2016
DOI: 10.1039/c5sm02371h
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of norfloxacin diffusion across bilayers on lipid composition

Abstract: Antibiotic resistance is a growing concern in medicine and raises the need to develop and design new drug molecules that can efficiently inhibit bacterial replication. Spurring the passive uptake of the drug molecules is an obvious solution. However our limited understanding of drug-membrane interactions due to the presence of an overwhelming variety of lipids constituting cellular membranes and the lack of facile tools to probe the bio-physical interactions between drugs and lipids imposes a major challenge t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 67 publications
(82 reference statements)
1
34
0
Order By: Relevance
“…However, the effect of the UWL on drug permeation is expected to be a function of velocity22, and we have previously shown that the permeability coefficients measured in our assay are independent of vesicle velocity4. Finally, we have used our assay to study the role of lipid composition on drug transport; we observed that simply changing the lipid molecules in the vesicle membranes from DPhPC to DOPC changed drug permeability by over an order of magnitude17. Thus the lipid membrane appears to be the rate limiting step to drug permeation in our assay.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…However, the effect of the UWL on drug permeation is expected to be a function of velocity22, and we have previously shown that the permeability coefficients measured in our assay are independent of vesicle velocity4. Finally, we have used our assay to study the role of lipid composition on drug transport; we observed that simply changing the lipid molecules in the vesicle membranes from DPhPC to DOPC changed drug permeability by over an order of magnitude17. Thus the lipid membrane appears to be the rate limiting step to drug permeation in our assay.…”
mentioning
confidence: 74%
“…Fluoroquinolones thus disrupt the DNA supercoiling process and inhibit bacterial cell division16. We have also studied the dependence of norfloxacin transport on the lipid composition of the membrane, and in particular investigated bilayers containing different types of lipid molecules commonly found in the cytoplasmic membrane of Escherichia coli 17. Our technique also enables direct measurements of drug uptake in proteoliposomes containing the E. coli outer membrane protein OmpF in the membrane; we thus quantified the role of these porins in norfloxacin transport18.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DPhPC is relatively adapted to study some biological processes like protein channel opening and closing . On the other hand, it has critical limitations that hinder its broader application to mimic physiological membranes, e.g., altered protein mobility, absence of lipids or protein domains, lack of local interaction between lipid and proteins . Nevertheless, any criteria regarding the composition, the fluidity, the accessibility, the stability, and the monitoring can be met by one of the existing setups.…”
Section: Introductionmentioning
confidence: 99%
“…[28] On the other hand, it has critical limitations that hinder its broader application to mimic physiological membranes, e.g., altered protein mobility, absence of lipids or protein domains, lack of local interaction between lipid and proteins. [29,30] Nevertheless, any criteria regarding the composition, the fluidity, the accessibility, the stability, and the monitoring can be met by one of the existing setups. However, a current limitation to the actual replication of physiological processes is that no technique can simultaneously validate all these criteria (see Supporting Note and Table S1, Supporting Information, for their detailed description and comparison).…”
Section: Introductionmentioning
confidence: 99%